Applications of Fixed-Point and Optimization Methods to the Multiple-Set Split Feasibility Problem - Yonghong Yao; Rudong Chen; Giuseppe Marino; Yeong Cheng Liou (Journal of Applied Mathematics)
The multiple-set split feasibility problem requires finding a point closest to a family of closed convex sets in one space such that its image under a linear transformation will be closest to another family of closed convex sets in the image space. It can be a model for many inverse problems where constraints are imposed on the solutions in the domain of a linear operator as well as in the operator’s range. It generalizes the convex feasibility problem as well as the two-set split feasibility problem. In this paper, we will review and report some recent results on iterative approaches to the multiple-set split feasibility problem.